Implementation of an RFID RC522 and IoT-Based Automatic Door Security System in an Electrical Engineering Laboratory - Wijanarko, Yudi; Alfarizal, Niksen; Pratama, Muhammad Regi (Indonesian Journal of Artificial Intelligence and Data Mining, 2025)
The development of smart home technology has encouraged the development of more efficient and integrated automatic security systems, Using RFID technology with the Internet of Things (IoT) is one method that can be applied. This research aims to implement an automatic door security system based on RFID RC522 connected to the IoT network in the Electrical Engineering Laboratory. The research method used is Research and Development (RnD) through the process of designing, making, and testing system prototypes. The system is controlled by an ESP32 microcontroller, uses an RC522 RFID module for authentication, and utilizes relays and solenoid door locks as locking mechanisms. Test results show that the maximum effective RFID reading distance is 5 cm, with a fast and accurate response at a distance of 1 to 4 cm. The system can log all access activities directly through the IoT platform and distinguish between valid and invalid cards. In terms of power consumption, the door lock solenoid has the largest power usage when active at 7.2 W, while other components remain efficient. The implementation of this system is proven to be able to improve the security aspects and ease of access monitoring in the laboratory room automatically and connected.